1992
DOI: 10.1016/0887-2333(92)90064-x
|View full text |Cite
|
Sign up to set email alerts
|

DNA adduct formation and 7-ethoxyresorufin O-deethylase induction in primary culture of rainbow trout hepatocytes exposed to benzo[a]pyrene

Abstract: Abstract--The formation of DNA adducts, using the 32p-postlabeiling assay, and induction of 7-ethoxyresorufin O-deethylase (EROD) were investigated in a primary culture of rainbow trout hepatocytes exposed to benzo[a]pyrene (B[a]P). Concentrations of 0.1 and 1/zM-B[a]P were shown to induce EROD whereas 10 #M was an inhibitory concentration. DNA adducts were detected for 12 hr to 72 hr after exposure to 1 #M-B[a]P whereas EROD activity was increased 36 hr after treatment. The pattern of adducts was shown to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 29 publications
2
10
0
1
Order By: Relevance
“…On the other hand, Peters et al (1997) clearly found a time delay between the increase of EROD activity and the formation of DNA adducts in juvenile turbot (Scophthalmus maximus) exposed to waterborne BaP. In addition, Masfaraud et al (1992) did not observe any correlation between EROD activity and level of DNA adducts in trout hepatocytes exposed in vitro to benzo[a]pyrene (BaP), suggesting a signi"cant involvement of conjugating and DNA repair enzymes in the regulation of DNA adduct formation and elimination. Such regulation must be taken into account, since stable adducts can form alkali-labile sites in DNA which may produce single strand breaks after alkali treatment in the Comet assay (Devaux et al, 1997).…”
Section: Multibiomarker Responses In Wild Fishmentioning
confidence: 94%
“…On the other hand, Peters et al (1997) clearly found a time delay between the increase of EROD activity and the formation of DNA adducts in juvenile turbot (Scophthalmus maximus) exposed to waterborne BaP. In addition, Masfaraud et al (1992) did not observe any correlation between EROD activity and level of DNA adducts in trout hepatocytes exposed in vitro to benzo[a]pyrene (BaP), suggesting a signi"cant involvement of conjugating and DNA repair enzymes in the regulation of DNA adduct formation and elimination. Such regulation must be taken into account, since stable adducts can form alkali-labile sites in DNA which may produce single strand breaks after alkali treatment in the Comet assay (Devaux et al, 1997).…”
Section: Multibiomarker Responses In Wild Fishmentioning
confidence: 94%
“…In the aquatic environment, the exposure of living organisms to xenobiotics leads to interactions between these chemicals and biological systems, which may give rise to biochemical disturbances or/and adaptive responses (Masfaraud et al 1992). Metabolism or biotransformation through the phase I (P450 monooxygenase enzymes) and phase II (conjugating enzymes) pathway are requisites for detoxification and excretion of lipophilic chemicals in aquatic animals (Goksøyr and Förlin 1992).…”
mentioning
confidence: 99%
“…Cell cultures have been used to study various aspects of teleost liver metabolism and toxicology, including temperature acclimation (Kennedy et al, 1991;Jensen et al, 1996), bile acid transport (Rabergh et al, 1994), nutrient metabolism and endocrine regulation (Hayashi and Ooshiro, 1986;Duan et al, 1993;Segner et al, 1994), hormone receptor expression (Mommsen and Lazier, 1986;Segner et al, 1993), vitellogenin synthesis (Maitre et al, 1986;Pelissero et al, 1993;Anderson et al, 1996), xenobiotic metabolism (Masfaraud et al, 1992;Pesonen et al, 1992;Miller et al, 1993;Scholz et al, 1997), chemical interaction with DNA (Gagn6 and Blaise, 1995;Segnel, 1994, 1997), biomarker expression (Hyllner et al, 1989;Grosvik and Gokscyr, 1996), or screening for aquatic pollutants (Braunbeck, 1993;Zahn and Braunbeck, 1993;Zahn et al, 1996). In the majority of these studies, monolayer cultures and simple media formulations were used without further consideration of the question how the selected culture conditions may have affected the physiology of the cells.…”
Section: Introductionmentioning
confidence: 99%